THEORETICAL AND METHODOLOGICAL ASPECTS OF INSURANCE CUSTOMER LOYALTY AND ITS CULTIVATION - Kindurys, Vytautas (Ekonomika, 2009)
The article, after the evaluation of opinion of various authors, first of all deals with the contents of loyalty of the insured and gives its definition. It also discusses theoretical questions of insurers’ benefits due to loyalty of the insured, a the benefits of the insured themselves. While examining the factors influencing satisfaction and loyalty of the insured the conclusion is made that the most important factors are the image of an insurance company, its reliability, the comprehended quality of the insurance services and their price, and the means of motivation of the insured. Furthermore, the article discusses the effect of the corresponding factors on the emotional and rational loyalty of the insured and on the formation of true loyalty of the insured. The article pays exceptional attention to such theoretical issues of implementation means and actions of cultivating loyalty of the insured as the functions of the system of means of loyalty cultivation, the strategies of loyalty cultivation (financial motivation, social relations, meeting of individual requirements, structural relations). p>